A Review of Non-Cooperative Game-Theoretic Control Strategies for Micro-Grids - Espina-Gonzalez, E; Diaz-Diaz, M; Plitt-Morales, M (Institute of Electrical and Electronics Engineers Inc., 2024)
The integration of renewable energy sources and the increasing complexity of power systems require advanced control strategies to ensure efficient and reliable operation. Non-cooperative game theory offers a framework for modeling competitive interactions among distributed energy resources. This paper reviews recent research to highlight the key features, benefits, and challenges associated with various non-cooperative control methods. It offers insights into their distinct characteristics and use cases, helping to identify the most suitable approach for specific micro-grid scenarios. © 2024 IEEE.